Examining language switching in bilinguals: The role of preparation time*. Issue 2 (2nd November 2015) - MOSCA, MICHELA; CLAHSEN, HARALD
Abstract : Much research on language control in bilinguals has relied on the interpretation of the costs of switching between two languages. Of the two types of costs that are linked to language control, switching costs are assumed to be transient in nature and modulated by trial-specific manipulations (e.g., by preparation time), while mixing costs are supposed to be more stable and less affected by trial-specific manipulations. The present study investigated the effect of preparation time on switching and mixing costs, revealing that both types of costs can be influenced by trial-specific manipulations.